2000
DOI: 10.1097/00001756-200004070-00003
|View full text |Cite
|
Sign up to set email alerts
|

Brain stem auditory evoked fields in response to clicks

Abstract: Magnetoencephalographic correlates of brain stem auditory evoked potentials (BAEP) have been identified by applying the model of a current dipole with invariant location and orientation (fixed dipole) to data recorded with a 37-channel first-order gradiometer system. In all three subjects studied, the dominating wave of the recorded brain stem auditory evoked field (BAEF) coincided exactly with wave V in the contralateral BAEP (maximal field amplitude of the order of 2-3 fT). In one subject, also a wave preced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…However, the field patterns indicated, as reported earlier [Lü tkenhö ner et al, 2000;Scherg and von Cramon, 1985], that a single equivalent current dipole may not be a satisfactory source for the later ABR/mABR waves as there probably are several simultaneously active generator sites in the neural structures. Furthermore, the different conductivities of the brain tissue (0.3 S/m employed here) and the cerebrospinal fluid [1.8 S/m; Baumann et al, 1997] in the fourth ventricle, close to the observed wave V source region, may contribute to the localization error.…”
Section: Source Modelingmentioning
confidence: 48%
See 1 more Smart Citation
“…However, the field patterns indicated, as reported earlier [Lü tkenhö ner et al, 2000;Scherg and von Cramon, 1985], that a single equivalent current dipole may not be a satisfactory source for the later ABR/mABR waves as there probably are several simultaneously active generator sites in the neural structures. Furthermore, the different conductivities of the brain tissue (0.3 S/m employed here) and the cerebrospinal fluid [1.8 S/m; Baumann et al, 1997] in the fourth ventricle, close to the observed wave V source region, may contribute to the localization error.…”
Section: Source Modelingmentioning
confidence: 48%
“…A set of virtual channels, sensing source currents without directional specificity, derived from a priori anatomical information about the assumed source location have successfully been used to recover the time course of a deep source [Tesche, 1996]. In addition, MEG measurements of the auditory brainstem responses have been demonstrated [Erné and Hoke, 1990;Erné et al, 1987;Iramina and Ueno, 1995;Lü tkenhö ner et al, 2000].…”
Section: Introductionmentioning
confidence: 99%
“…In the electric case the ECD is described by the Gabor-Nelson equations [8], [9] resulting from Eq. (2). The moment of the ECD is given by the electric dipole moments, i. e., (6) The location of the ECD is described by a System of five equations obtained from the electric quadrupole moments.…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that the amplitude of the P50 component of the AEP of succeeding stimuli was much smaller than that of the preceding stimuli when lSI was less than 500 ms. Liitkenhoner [13,14] studied the auditory evoked magnetic fields (AEF) with magnetoencephalography (MEG) in normal subjects when receiving paired sound stimulus. Judd [5] studied the specific sensory gating deficits in schizophrenic patients.…”
mentioning
confidence: 99%